Analisis Problematika Perencanaan Dan Pelaksanaan Pembelajaran Daring Guru PPKN SMA Kota Solok - Ifnindira Ifnindira; Hasrul Piliang (At-Ta'lim : Media Informasi Pendidikan Islam, 2021)
Abstract: Analysis of the Problems of Planning and Implementation of Online Learning for Civic Education Teachers in Solok CityThis study analyzes the problems of planning and implementing online learning for Civics teachers at SMA Negeri Solok City during the COVID 19 pandemic. The purpose of this study is to describe the difficulties of Civics teachers in planning and implementing online learning at SMA Negeri Solok City and finding solutions. Based on the analysis of the research results, it is concluded: 1) The initial problem in planning online learning is that all teachers have not been able to analyze, choose, determine strategies and online learning methods and have not supported the ability of teachers. to use IT tools; 2). The initial problem in the implementation of online learning (PJJ) is that the ability to create classes, manage and evaluate classes that are integrated with the ability to use and experience mastery of IT tools for the implementation of distance learning; 3) Efforts to overcome obstacles in planning and implementing online learning at SMA Negeri Solok City are by participating in socialization activities, technical guidance, online training that improves pedagogic competence and online learning professional competence (PJJ). The implication of the research is that the analytical ability of teachers in selecting, determining learning strategies and methods and using IT tools for planning and implementing distance learning is very important to improve because efforts to increase teacher pedagogic and professional competencies will have an impact on improving the quality of learning. classroom learningAbstract: Analisis Problematika Perencanaan Dan Pelaksanaan Pembelajaran Daring Guru PPKN SMA Kota SolokPenelitian ini menganalisis problematika perencanaan dan pelaksaan pembelajaran daring Guru PPKn SLTA Kota Solok saat pandemi COVID 19. Tujuan penelitian ini adalah mendeskripsikan kesulitan guru PPKn dalam merencanakan dan melaksanakan pembelajaran daring di SLTA Kota Solok dan mencarikan solusi pemecahannya. Berdasarkan analisis hasil penelitian disimpulkan: 1) Masalah awal dalam perencanaan pembelajaran daring belum mampunya seluruh guru untuk menganalisis, memilih, menetapkan strategi dan metode pembelajaran daring serta belum mendukungnya kemampuan guru dalam menggunakan perangkat TI; 2). Masalah awal dalam pelaksanaan pembelajaran daring (PJJ) belum optimalnya kemampuan pembuatan kelas, pengelolaan kelas dan evaluasi yang terintegrasi dengan kemampuan penggunaan dan pengalaman penguasaan perangkat TI untuk pelaksanaan pembelajaran jarak jauh; 3) Upaya untuk mengatasi kendala dalam perencanaan dan pelaksanaan pembelajaran daring di SLTA Kota Solok adalah mengikuti kegiatan sosialisasi, bimbingan teknis, pelatihan on line yang meningkatkan kompetensi pedagogik dan kompetensi profesional pembelajaran daring (PJJ). Implikasi penelitian bahwa kemampuan analisis guru dalam memilih, menetapkan strategi dan metode pembelajaran serta penggunakan perangkat TI untuk perencanaan dan pelaksanaan pembelajaran jarak jauh sangat penting ditingkatkan karena upaya peningkatan kompetensi pedagogik dan profesional guru akan berdampak pada peningkatan kualitas pembelajaran dikelas